2003
DOI: 10.1007/s11605-003-0036-6
|View full text |Cite
|
Sign up to set email alerts
|

Binding pancreaticojejunostomy: 150 consecutive cases without leakage

Abstract: The objective of this study was to verify the safety of a new technique termed "binding pancreaticojejunostomy" in a prospective cohort study. Pancreaticojejunal anastomostic leakage is a major cause of morbidity and mortality after pancreaticoduodenectomy. To prevent the development of pancreatic fistulas, we designed a special technique that we termed binding pancreaticojejunostomy. Binding pancreaticojejunostomy entails binding 3 cm of the serosamuscular sheath of the jejunum to the intussuscepted pancreati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 12 publications
0
58
1
2
Order By: Relevance
“…1,13 Several techniques have been described for safe surgical management of the pancreatic remnant, including main duct stenting, pancreaticogastrostomy, and pancreaticojejunostomy with duct to mucosa anastomosis or intussusception, but none has a clearly proven superiority over the others and subsequently became widely accepted. 10,[17][18][19][20][21][22] Recently, Peng et al 23,24 described a new anastomosis technique, called binding pancreaticojejunostomy (BPJ).…”
Section: Introductionmentioning
confidence: 99%
“…1,13 Several techniques have been described for safe surgical management of the pancreatic remnant, including main duct stenting, pancreaticogastrostomy, and pancreaticojejunostomy with duct to mucosa anastomosis or intussusception, but none has a clearly proven superiority over the others and subsequently became widely accepted. 10,[17][18][19][20][21][22] Recently, Peng et al 23,24 described a new anastomosis technique, called binding pancreaticojejunostomy (BPJ).…”
Section: Introductionmentioning
confidence: 99%
“…The median duration of surgery of 88 patients was 3.8 h (range 3-6.5) and the median time to perform pancreaticojejunostomy was 13.3 min (range [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The median blood loss was 750 ml (range 300-1,800), 36 of 88 patients needed transfusion and the median blood transfusion for 56 patients was 380 mL (range 200-1,200).…”
Section: Resultsmentioning
confidence: 99%
“…When compared with other studies [27][28][29][30][31][32][33], we found that the results of present study were much better and very encouraging. Except of the above-mentioned, the advantages of our technique are: (1) simple, only two to three transpancreatic U-sutures are placed; (2) easy, no need of isolation of long segment of remnant pancreas as described by Peng et al [25], pancreatic stump could be easily invaginated into the jejunum loop through straining the Usutures; (3) rapid, the median time to perform pancreaticojejunostomy using this technique was only 13.3 min (range [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A number of technical interventions have been suggested to decrease the rate of pancreatic fistula after pancreatic surgery without an accepted consensus [17][18][19][20][21][22][23][24]. The pharmacological approach to prevent anastomotic leak after pancreatic surgery was first described by a German group who reported a reduced morbidity after pancreaticoduodenectomy with perioperative infusion of somatostatin [25].…”
Section: Introductionmentioning
confidence: 99%